Numerical integration rules for multivariate inversions - Shephard, N (Taylor and Francis, 1991)
Working from a known characteristic function, integration rules for the computation of the multivariate distribution function are derived. Procedures for the automatic selection of step sizes are one particular strength of the proposed method. Examples of the use of the procedure are given.